1999
DOI: 10.1002/(sici)1521-4141(199905)29:05<1692::aid-immu1692>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired apoptotic deletion of myelin basic protein-reactive T cells in patients with multiple sclerosis

Abstract: T cell responses to myelin basic protein (MBP) may play an important role in the pathogenesis of multiple sclerosis (MS). If MBP-reactive T cells are involved in the disease processes and undergo clonal activation and expansion, their precursor frequency would be increased in patients with MS. The frequency of MBP-reactive T cells is also influenced by regulatory mechanisms in vivo, including apoptotic deletion. In this study, we examined changes in the frequency of MBP-reactive T cells in patients with MS as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Among several hypotheses on the pathogenesis of MS, defective AICD of myelin-reactive T cells may play a central role. Interference of IFN-b with this hindered CD95L-induced apoptosis is a possible mechanism of action, and the increase of CD95L by IFN-b may support increased apoptosis of autoreactive T cells [20]. Statins would be desirable candidates for a long-term treatment in MS with regard to potentially favourable immunoregulatory effects, oral administration, safety profile and advantageous cost/benefit profile.…”
Section: Discussionmentioning
confidence: 99%
“…Among several hypotheses on the pathogenesis of MS, defective AICD of myelin-reactive T cells may play a central role. Interference of IFN-b with this hindered CD95L-induced apoptosis is a possible mechanism of action, and the increase of CD95L by IFN-b may support increased apoptosis of autoreactive T cells [20]. Statins would be desirable candidates for a long-term treatment in MS with regard to potentially favourable immunoregulatory effects, oral administration, safety profile and advantageous cost/benefit profile.…”
Section: Discussionmentioning
confidence: 99%
“…It may be relevant that a proportion of MBP-reactive TCL, specific for region 111-139, were susceptible to apoptosis in vitro following stimulation with MBP [15]. Furthermore, these Fas-sensitive MBP-specific T cells were not deleted in vivo in patients with MS as opposed to healthy individuals [15]. This argument clearly does not hold for all epitopes since we have managed to obtain TCC for many different MBP epitopes.…”
Section: Controlmentioning
confidence: 96%
“…Interestingly, even though residues 90-114 and, to a lesser extent, 15-39 were recognized frequently by MS patients, TCC specific for these determinants have yet to be developed in vitro. It may be relevant that a proportion of MBP-reactive TCL, specific for region 111-139, were susceptible to apoptosis in vitro following stimulation with MBP [15]. Furthermore, these Fas-sensitive MBP-specific T cells were not deleted in vivo in patients with MS as opposed to healthy individuals [15].…”
Section: Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports published recently suggested impaired apoptotic deletion of MBP-reactive T cells in the peripheral blood of patients with MS. Zang et al (514) demonstrated that a significant proportion of T cells in the peripheral blood of patients with MS, which are specific for MBP, are sensitive to FasL-mediated apoptosis but are not deleted in vivo. Defective apoptotic deletion of mitogen-stimulated T lymphocytes in the peripheral blood of patients with MS has been reported by several groups of investigators.…”
Section: Apoptosis Of T Cells In Patients With Msmentioning
confidence: 99%